Effects of exercise during pregnancy on postpartum depression: a meta-analysis - Yuanyuan Wang; Mengtin Pan; Baojian Wei; Huiwen Sun; Jing Huang (Quality in Sport)
Background: Postpartum depression is a pervasive depressive episode in the postpartum period that adversely affects the mother, her partner, mother-infant interaction, and offspring development. There are many limitations in the treatment of postpartum depression, which makes prevention during pregnancy important. Exercise has many brain and psychological benefits, but current results are inconsistent as to whether exercise during pregnancy prevents postpartum depression.